Modern electron microscopy in the study of chemical systems at the boundary of organic synthesis and catalysis. (29th November 2016) - Bukhtiyarov, V I; Zaikovskii, V I; Kashin, A S; Ananikov, V P
Abstract: Electron microscopy, which has become a routine tool of materials science, heterogeneous catalysis, metallurgy and some other areas, is currently attracting increasing attention of researchers working in the area of fine organic synthesis. The modern capabilities for direct visualization of micro- and nano-objects suitable for characterization of electron beam-sensitive molecular and hybrid organic systems extend the scope of applicability of electron microscopy in chemistry. The review describes representative examples of electron microscopic investigations at the boundary of organic synthesis and catalysis. The bibliography includes 114 references.